Insights into ceramic use in prehistoric Northwest China obtained from residue analysis: a pilot study on the Andersson Collection at the Museum of Far Eastern Antiquities, Stockholm - Keute, J; Isaksson, S; Deviese, T; Hein, A (Ostasiatiska Museet, 2021)
The Andersson Collection housed at the Museum of Far Eastern Antiquities holds finds from the earliest archaeological fieldwork ever conducted in northwest China. Recent years have seen an increased interest in the archaeology of that region, especially prehistoric subsistence practices and their environmental correlates. The Andersson Collection which has lain largely dormant since the 1940s provides a great opportunity for further research on this topic, especially on sites which are no longer accessible for a variety of reasons. As part of a larger project aimed at “re-excavating” these materials from museum storage and answer questions of identity and interaction along the old exchange corridor of the proto-Silk Road, this pilot study explores the potential of using molecular and isotopic characterization of organic residues from Neolithic and Bronze Age ceramic vessels to understand subsistence practices in northwest China. Organic residue analysis can aid our understanding what kinds of foodstuffs these vessels held and shed light on cooking and eating habits and how these practices change or remain consistent over time and/or space. There is some concern that long-term storage in potentially unsuitable containers, cleaning with harsh chemicals, or restauration methods deemed suitable at the time may have destroyed much of the residue. Indeed, this pilot study finds that there is a considerable amount of contaminants in all samples, however, some residue has been observed and analysed, suggesting that more advanced extraction methods combined with an investigation into museum records to find out about previous cleaning and restauration methods, may help mitigate these issues. A similar approach may also be applied to other legacy collections.